Anti-neoplastic activity of holothuria arenicola saponin against erlich ascites carcinoma in swiss albino mice - Shimaa Anter Mahmoud; Amel Mahmoud Soliman; Ayman Saber Mohamed (Cairo : Shimaa Anter Mahmoud, 2020)
Cancer is a complex disease including various changes in cell physiology, which may lead to malignant tumors. The Ehrlich tumor is a quickly developing carcinoma with aggressive behavior. Saponins are important bioactive compounds in sea cucumbers that have an antioxidant, anti-microbial, anti-inflammatory, antiproliferative, and anti-tumor effect. The present investigation attempted to study the potential use of the Holothuria arenicola saponin (HaS) against Ehrlich Ascites Carcinoma (EAC) tumor model in female Swiss albino mice. Forty female Swiss albino mice were divided into four main groups (10 mice/group). Control, EAC, 5-fluorouracil (5-FU) and HaS treated groups. Control group daily injected intraperitoneally with 0.2 ml physiological saline from 0th day till the end of the experiment (10th day). Rest groups were inoculated with EAC cells (5 {u00D7} 10p6 (Bcells/mouse i.p.) at 0th day. Mice injected intraperitoneally with, 0.2 ml physiological saline (EAC), 5-FU (20 mg/kg) (5- FU) and saponin (120 mg/kg) (HaS) for 9 consecutive days. The HPLC studies of the extracted saponin showed the peak at retention time 5.19 min. was matched with the standard saponin with a total amount of 34.87%. HaS group showed a reduction in the Erlich ascetic volume (EAV), tumor cell count, the viability of tumor cells, and the activities of arginase, aspartate aminotransferase (AST), alanine aminotransferase (ALT), alkaline phosphatase (ALP) and creatinine, urea, uric, white blood cells (WBCs) and malondialdehyde (MDA).While it caused a general increase in the levels of hemoglobin (Hb), red blood cells (RBCs), platelets (Plt) and the activities of glutathione-S-transferase (GST), catalase (CAT) and glutathione reduced (GSH).The histopathological investigation showed clear improvement in the hepatic and kidney architecture. The results of this study clearly investigated that HaS is a potent natural product that has promising antineoplastic efficacys
Thesis (M.Sc.) - Cairo University - Faculty of Science - Department of Zoology
Issued also as CD
Keywords: Holothuria arenicola; Saponin; Sea cucumber